Suami isteri naik haji : kembara Raja Shahabuddin dan Rahmah 1939-1940 - Lubis, Abdur-Razzaq; Khoo, Salma Nasution; Tengku Ahmad Hazri (Pulau Pinang : Areca Books, 2023)
Transliteration of Jawi script on journal of the journey to Mecca for Hajj by Raja Shahabudin on years 1939-1940.
Includes bibliographic references and index.
Keywords: Muslim pilgrims and pilgrimages -- Malaysia -- Diaries; Muslim pilgrims and pilgrimages -- Saudi Arabia -- Mecca; Muslim pilgrims and pilgrimages -- Description and travel